Analisis Parenting Self Efficacy Orang Tua Dalam Mendidik Kemandirian Anak Difabel Berprestasi Di SLB Negeri Deli Serdang - Salwa Rizky Adinda; Erni Asneli Erni (LPPM UNISDA, 2026)
This study aims to analyse parents’ parenting self-efficacy (PSE) in fostering independence in high-achieving children with disabilities at the Deli Serdang State Special School. This study employs a qualitative method using a case study approach. The research informants comprised five main informants—namely, three parents of high-achieving children with disabilities and two parents of children with disabilities who had not yet achieved academic success—three key informants from the Deli Serdang State Special School, and five additional informants selected through purposive sampling. Data were collected through in-depth interviews, observation and documentation, using source triangulation techniques. The research findings indicate that parents of high-achieving children with disabilities possess a stronger PSE based on Coleman and Karraker’s five dimensions: achievement, recreation, caregiving, health, and discipline. Parents play an active role in supporting their children’s development through academic support, meeting emotional needs, managing health, and developing their children’s potential. The difference between parents of high-achieving children and those of children who have not yet achieved is evident in the quality of parenting practices, rather than in the affection shown. Parental Self-Efficacy is influenced by parents’ acceptance of their child’s condition, experiences of success, social support, and belief in their child’s abilities. This study recommends strengthening parental support programmes and family support through schools and the community.